Arab celebrities’ politeness strategies in selected ‘talk to Al Jazeera’ talk shows - Taha, Taha Mahmood (2018)
When people communicate they usually perform various speech acts such as giving compliments, apologizing, thanking, and making requests. The performance of these speech acts most often involves different types of politeness strategies. The present research focuses on investigating how the Arabs use English language in TV talk shows to express politeness. The main purpose of this study is classifying the speech act categories and analysing the politeness strategies performed by Arab celebrities in talk shows. Also, it aims to examine the linguistic expressions used within the speech act categories as well the politeness strategies. The dearth of studies which were conducted to identify the politeness strategies and speech act categories used by Arab celebrities during talk shows was the main reason behind doing this study. Seven episodes from the ‘Talk to Al Jazeera’ talk show were downloaded from YouTube and transcribed by the researcher. The data were analysed according to Searle’s (1976) speech act theory and Brown and Levinson (1987) politeness theory. The study is a qualitative study and a discourse analysis approach was used to analyse data. The study was conducted at the Faculty of Modern Languages and Communication at Universiti Putra Malaysia (UPM). The results of the study revealed that the Arab celebrities tended to use more positive politeness strategies than other strategies. It also showed that they used representative speech acts more than the other categories. Furthermore, they used different linguistic expressions within speech act categories and politeness strategies during the talk shows. The findings of the study showed that the Arab celebrities tended to use narrative during the talk shows. Also, the findings revealed that the celebrities tended to use the inclusive (i.e., we) form to include both the speaker and the hearer in the activity during their speech. The findings of the current study provide some useful insights into how the Arab speakers utilise politeness strategies when they interact in English in TV talk shows and serve as a guide for ESL and EFL users in avoiding conflict when interacting with others.